2010
DOI: 10.1155/2010/620503
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Decellularization Protocol on the Mechanical Behavior of Porcine Descending Aorta

Abstract: Enzymatic-detergent decellularization treatments may use a combination of chemical reagents to reduce vascular tissue to sterilized scaffolds, which may be seeded with endothelial cells and implanted with a low risk of rejection. However, these chemicals may alter the mechanical properties of the native tissue and contribute to graft compliance mismatch. Uniaxial tensile data obtained from native and decellularized longitudinal aortic tissue samples was analyzed in terms of engineering stress and fit to a modi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(52 citation statements)
references
References 57 publications
(98 reference statements)
3
47
0
2
Order By: Relevance
“…The xenograft that underwent the first protocol showed complete decellularization but with a much distorted ECM. Valves treated with Triton X-100 showed a completely cell-free structure across the complete thickness of the valve leaflet, which is consistent with earlier results by Bader et al [6] Triton X-100 disrupts lipid-lipid and lipidprotein interactions while leaving protein-protein interactions intact.…”
Section: Discussionsupporting
confidence: 91%
“…The xenograft that underwent the first protocol showed complete decellularization but with a much distorted ECM. Valves treated with Triton X-100 showed a completely cell-free structure across the complete thickness of the valve leaflet, which is consistent with earlier results by Bader et al [6] Triton X-100 disrupts lipid-lipid and lipidprotein interactions while leaving protein-protein interactions intact.…”
Section: Discussionsupporting
confidence: 91%
“…'Waste materials' from animal slaughterhouses, such as porcine skin or arterial vessels, have also been noted as enabling the creation of high quality bio-natural matrices which deliver significant results [29]. Decellularization procedures carried out on such materials can be adapted to create optimal results, notably via the creation of acellular matrices [30].…”
Section: Plant-derived Human Collagen Scaffolds (Pdhc)mentioning
confidence: 99%
“…Of particular interest was the work of Fitzpatrick et al (2010), who described the decellularization of a porcine descending aorta by using 0.25% sodium-deoxycholate. Since we could not reproduce this condition for a complete decellularization of the arteries, we changed the incubation time and the composition of the chemicals in different steps and found that a high working concentration (4%) of the ionic detergent sodium-deoxycholate in combination with a low amount of the non-ionic detergent Triton X-100 led to complete decellularization.…”
Section: A B Cmentioning
confidence: 99%